Short communication: Birth Shock! - Susan Hogan; Rebecca Ashley (Elsevier, 2023)
Birth Shock! is an AHRC-funded (AH/K003364/1) engagement-focused project exploring and enhancing the impact and reach of The Birth Project (AH/V000926/1). This study is particularly concerned with the role the arts can play in the perinatal period, especially in supporting the wellbeing of new mothers. In particular, we wished to assess the role of a suite of films exploring this subject with trainee and health-professional audiences.